Bioimpedance spectroscopy for assessment of volume status in patients before and after general anaesthesia. - Matthäus Ernstbrunner; Lisa Kostner; Oliver Kimberger; Peter Wabel; Marcus Säemann; Klaus Markstaller; Edith Fleischmann; Barbara Kabon; Manfred Hecking (PLoS ONE, 2014)
Background Technically assisted assessment of volume status before surgery may be useful to direct intraoperative fluid administration. We therefore tested a recently developed whole-body bioimpedance spectroscopy device to determine pre- to postoperative fluid distribution. Methods Using a three-compartment physiologic tissue model, the body composition monitor (BCM, Fresenius Medical Care, Germany) measures total body fluid volume, extracellular volume, intracellular volume and fluid overload as surplus or deficit of 'normal' extracellular volume. BCM-measurements were performed before and after standardized general anaesthesia for gynaecological procedures (laparotomies, laparoscopies and vaginal surgeries). BCM results were blinded to the attending anaesthesiologist and data analysed using the 2-sided, paired Student's t-test and multiple linear regression. Results In 71 females aged 45 ± 15 years with body weight 67 ± 13 kg and Duration of anesthesia 154 ± 69 minutes [corrected] duration of anaesthesia 154 ± 68 min, pre- to postoperative fluid overload increased from -0.7 ± 1.1 L to 0.1 ± 1.0 L, corresponding to -5.1 ± 7.5% and 0.8 ± 6.7% of normal extracellular volume, respectively (both p<0.001), after patients had received 1.9 ± 0.9 L intravenous crystalloid fluid. Perioperative urinary excretion was 0.3 ± 0.2 L [corrected]. The increase in extracellular volume was paralleled by an increase in total body fluid volume, while intracellular volume increased only slightly and without reaching statistical significance (p = 0.15). Net perioperative fluid balance (administered fluid volume minus urinary excretion) was significantly associated with change in extracellular volume (r(2) = 0.65), but was not associated with change in intracellular volume (r(2) = 0.01). Conclusions Routine intraoperative fluid administration results in a significant, and clinically meaningful increase in the extracellular compartment. BCM-measurements yielded plausible results and may become useful to guide intraoperative fluid therapy in future studies.